Ten-minute warm-up in hot climate best assists thermal comfort, muscular power output, and fatigue, during soccer-specific repeated-sprint ability - Chaâri, N.; Frikha, M. (Biology of Sport, 2022)
Structuring warm-up (WU) in hot climate conditions before high-intensity efforts is still drawing the attention of researchers and practitioners. The present study investigates the effect of two WU durations (i.e.10 min: WU10 and 20 min: WU20) in a hot climate (~31°C), on thermal comfort, muscular power output and fatigue after a repeated-sprint test (RSA) in soccer players. Twelve amateur soccer players (age = 21.13 ± 1.8 years; height = 172.5 ± 4.6 cm and weight = 70.8 ± 5.1 kg) participated in a crossover randomized study, and they underwent a soccer-specific RSA test, after two WU durations and on different days. Peak power (PP), mean power (MP) and the fatigue index (FI) were calculated and analysed. Likewise, thermalcomfort/discomfort (TC), tympanictemperature (Ttym) and rating of perceived exertion (RPE) were recorded at rest, after WU and after RSA. The ANOVA showed a significant increase in MP after WU10 in comparison to WU20 by 1.9%, while PP remained similar between the two durations. A significant decline in muscular power in WU20 compared to WU10 appeared from the 5th sprinting repetition and continued to the end of the RSA. The WU20,compared to the WU10, produced higher RPE at post-WU (p < 0.001) and post-RSA (p = 0.018), and higher thermal discomfort sensation in both post-WU (p = 0.022) and post-RSA (p = 0.007) point of measures.Larger increases in Ttym were recorded after WU20 compared to WU10. WU10 in a hot climate (~31°C) best assists mean power output during soccer RSA, but not peak power. Extending the WU duration up to 20 min in a hot climate was revealed to be detrimental for muscular power output, inducing excessive thermal discomfort and fatigue. Therefore, it is important that trainers and soccer players carefully consider WU duration prior to competitions and training sessions in a hot climate, to optimize physiological responses.